Thermodynamic study of thunderstorms in southwestern Iran - asal falak; reza boran; farideh asadian (تحقیقات کاربردی علوم جغرافیایی)
This study aimed to investigate the temporal-spatial and synoptic features of thunderstorms in southwest of Iran (Khuzestan, Chaharmahal & Bakhtiari and Kohkiluyeh & Boyerahmad Provinces) It was compiled using volatility indices during the period 1985-2015. Results of Frequency Analysis of Thunderstorms at Dezful Station with 479 cases the highest frequency and Ramhormes with 252 days had the lowest frequency. In terms of seasonal distribution, spring was the most abundant with 39%. On a monthly basis, April had the lowest frequency with 21% and August with only 2 cases. In terms of thunderstorms the highest frequency of thunderstorms with no thunder was 21 percent. Synoptic analysis: Most of the time there is a nave (at level 500) or low pressure in the west of the region, east of the Mediterranean Sea with its tabs clockwise. From the Red Sea and the Persian Gulf, they entered the south, southwest, and west of Iran On the other hand, the high-pressure system on the Gulf of Aden in the east of the region is round in the clock It has injected moisture, especially at a level of 850 millibars. Interaction between the two systems over the course of the day, It has injected moisture from three sources of the Mediterranean Sea, the Red Sea and then the Persian Gulf into the rising systems of the region. The low-pressure counterclockwise movement of the eastern Mediterranean, Along with the high-altitude clock movement over the Gulf of Aden, it has injected moisture at levels of 850 to 700 degrees.